Patients' Reported Reasons for Non-Use of an Internet-Based Patient-Provider Communication Service: Qualitative Interview Study - Varsi, Cecilie; Gammon, Deede; Wibe, Torunn; Ruland, Cornelia M (JMIR Publications, 2013)
BackgroundThe adoption of Internet-based patient-provider communication services (IPPC) in health care has been slow. Patients want electronic communication, and the quality of health care can be improved by offering such IPPCs. However, the rate of enrollment in such services remains low, and the reasons for this are unclear. Knowledge about the barriers to use is valuable during implementation of IPPCs in the health care services, and it can help timing, targeting, and tailoring IPPCs to different groups of patients. ObjectiveThe goal of our study was to investigate patients' views of an IPPC that they could use from home to pose questions to nurses and physicians at their treatment facility, and their reported reasons for non-use of the service. MethodsThis qualitative study was based on individual interviews with 22 patients who signed up for, but did not use, the IPPC. ResultsPatients appreciated the availability and the possibility of using the IPPC as needed, even if they did not use it. Their reported reasons for not using the IPPC fell into three main categories: (1) they felt that they did not need the IPPC and had sufficient access to information elsewhere, (2) they preferred other types of communication such as telephone or face-to-face contact, or (3) they were hindered by IPPC attributes such as login problems. ConclusionsPatients were satisfied with having the opportunity to send messages to health care providers through an IPPC, even if they did not use the service. IPPCs should be offered to the patients at an appropriate time in the illness trajectory, both when they need the service and when they are receptive to information about the service. A live demonstration of the IPPC at the point of enrollment might have increased its use. Trial RegistrationClinicalTrials.gov NCT00971139; http://clinicaltrial.gov/ct2/show/NCT00971139 (Archived by WebCite at http://www.webcitation.org/6KlOiYJrW).